Germline mosaicism does not explain the maternal age effect on trisomy. Issue 10 (15th August 2013) - Rowsey, Ross; Kashevarova, Anna; Murdoch, Brenda; Dickenson, Carrie; Woodruff, Tracey; Cheng, Edith; Hunt, Patricia; Hassold, Terry
Abstract A variety of hypotheses have been proposed to explain the association between trisomy and increasing maternal age in humans, virtually all of which assume that the underlying mechanisms involve meiotic errors. However, recently Hultén and colleagues [Hulten et al., 2010b] proposed a provocative model—the Oocyte Mosaicism Selection Model (OMSM)—that links age‐dependent trisomy 21 to pre‐meiotic errors in the ovary. Specifically, they propose that nondisjunctional events occur in a proportion of germ cells as they mitotically proliferate, resulting in mosaicism for trisomy 21. Assuming that the presence of an additional chromosome 21 delays meiotic progression, these cells would be ovulated later in reproductive life, resulting in an age‐dependent increase in aneuploid eggs. Because this model has important clinical implications, we initiated studies to test it. We first analyzed oocytes from two trisomy 21 fetuses, combining immunostaining with FISH to determine the likelihood of detecting the additional chromosome 21 at different stages of meiosis. The detection of trisomy was enhanced during the earliest stage of prophase (leptotene), before homologs synapsed. Accordingly, in subsequent studies we examined the chromosome content of leptotene oocytes in seven second trimester female fetuses, analyzing three chromosomes commonly associated with human trisomies (i.e., 13, 16, and 21). In contrast to the prediction of the OMSM, we found no evidence of trisomy mosaicism for any chromosome. We conclude that errors in pre‐meiotic germ cells are not a major contributor to human aneuploidy and do not provide an explanation for the age‐related increase in trisomic conceptions. © 2013 Wiley Periodicals, Inc.